PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA PhET SIMULATION TERHADAP PENINGKATAN PEMAHAMAN KONSEP IPA SISWA KELAS IV SEKOLAH DASAR : [THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL ASSISTED BY PhET SIMULATION MEDIA ON THE IMPROVEMENT OF SCIENCE CONCEPT UNDERSTANDING OF FOURTH GRADE ELEMENTARY SCHOOL STUDENTS] - Isna Handayani; Fitri Nuraeni; Wina Mustikaati (Polyglot, 2026)
This research was motivated by science learning in elementary schools which is still teacher-centered and lacks the support of interactive learning media, resulting in students’ conceptual understanding not being optimal. This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by PhET Simulation media on improving students’ understanding of science concepts compared to the Discovery Learning model assisted by energy transformation card media. This study used a quasi-experimental method with a non-equivalent control group design. The research sample consisted of 37 students in the experimental class and 37 students in the control class. Data were collected through tests in the form of pre-tests and post-tests on science concept understanding, as well as non-test techniques in the form of documentation. The results showed that students’ understanding of science concepts in the experimental class improved higher than in the control class. The average pre-test score of the experimental class increased from 45 to 70.78 in the post-test, while the control class increased from 46.14 to 54.16. These results indicate that the Contextual Teaching and Learning (CTL) model assisted by PhET Simulation media affects the improvement of students’ understanding of science concepts on the topic of energy transformation. Therefore, the Contextual Teaching and Learning (CTL) model assisted by PhET Simulation media can be used as an alternative for science learning in elementary schools. Abstrak Bahasa Indonesia Penelitian ini dilatarbelakangi oleh pembelajaran IPA di sekolah dasar yang masih berpusat pada guru dan kurang didukung media pembelajaran interaktif sehingga pemahaman konsep siswa belum optimal. Penelitian ini bertujuan untuk mengetahui pengaruh model Contextual Teaching and Learning (CTL) berbantuan media PhET Simulation terhadap peningkatan pemahaman konsep IPA siswa dibandingkan model Discovery Learning berbantuan media kartu transformasi energi. Penelitian menggunakan metode kuasi eksperimen dengan desain non-equivalent control group design. Sampel penelitian terdiri atas 37 siswa kelas eksperimen dan 37 siswa kelas kontrol. Pengumpulan data dilakukan melalui tes berupa pre-test dan post-test pemahaman konsep IPA serta non-tes berupa dokumentasi. Hasil penelitian menunjukkan bahwa pemahaman konsep IPA siswa pada kelas eksperimen mengalami peningkatan lebih tinggi dibandingkan kelas kontrol. Nilai rata-rata pre-test kelas eksperimen sebesar 45 meningkat menjadi 70,78 pada post-test, sedangkan kelas kontrol dari 46,14 menjadi 54,16. Hasil tersebut menunjukkan bahwa model Contextual Teaching and Learning (CTL) berbantuan media PhET Simulation berpengaruh terhadap peningkatan pemahaman konsep IPA siswa pada materi transformasi bentuk energi. Oleh karena itu, model Contextual Teaching and Learning (CTL) berbantuan media PhET Simulation dapat dijadikan alternatif pembelajaran IPA di sekolah dasar.